Algérie, images d'un combat . Algeria, Images of a Fight - Laffont, Jérôme (Sourat Films Co. ; Centre de l'Audiovisuel à Bruxelles, 2009)
Verzio FF Duration: 00:52:00 As with all later conflicts, the Algerian War of Independence in the early 1960’s became a high-stakes target in the battle of competing images. Behind the war itself was a media war which was almost as crucial in contesting the sympathy of the world for the opposing points of view. As a counter to the propaganda movies made in support of the French military campaign, a few directors such as René Vautier devoted themselves to documenting the struggle from behind the lines with the independence fighters. Much of this footage – at times moving and at times harrowing, often very beautiful – was banned in France. Much of it has been lost and some even destroyed. A compelling film which raises important questions about the power of filmmaking and the purposes it serves in documenting – or manipulating – reality.